A Blockchain-Based Digital Library System Integrated with CryptoJS for Enhanced Security and Transparency - Evwiekpaefe, Abraham Eseoghene; Chinyio, Darius Tienhua; Ajakaiye, Fiyinfoluwa; Aleke, Paschal Obioma (Journal of Information Systems and Informatics, 2025)
In the context of digital library systems, blockchain presents a promising framework for enhancing the security, integrity, and transparency of operations such as book transactions, cataloging, and user authentication.  Library systems face several challenges, including lack of transparency and security vulnerabilities. Previous research efforts have explored various centralized digital library management systems, but they often suffer from single points of failure and insufficient security measures. The methodology involves integrating blockchain technology using CryptoJS for advanced encryption and hashing, the backend was designed using PHP (Laravel), while the technologies used in the front end includes HTML, CSS and Javascript. The blockchain technology was implemented using Cryptojs which provides security by implementing AES encryption to safeguard user credentials and book transaction records, preventing unauthorized usage. The system was tested in a digital library environment and diverse user set, where results demonstrated enhanced data security and improved operational efficiency. The system is scalable and adaptable to academic, research, and public libraries, providing real-time verification of transactions and enhanced protection against unauthorized access. By combining blockchain’s immutability with strong encryption and modern web technologies, the platform delivers a secure, transparent, and future-ready solution for digital library management with 88% effectiveness. Findings indicate that the proposed blockchain-integrated system not only resolves existing issues in digital library management, but also introduces new opportunities for innovation, including real-time transaction verification and improved trust among users.
Keywords: Blockchain; CryptoJs; Library System; Javascript; Database